Reacquisition of a functional early region by a mouse transformant containing only defective simian virus 40 DNA. - Chen, S (1984)
Viral DNA in simian virus 40-transformed mouse cells is capable of rearranging with passage. In this report, we show that such rearrangement can include an alteration in viral protein expression. SVT2, a simian virus 40-transformed mouse BALB/c 3T3 cell line, synthesizes only a super T antigen of molecular weight 100,000 without synthesizing the lytic-size large T or small t antigens with molecular weights of 94,000 and 17,000, respectively. Analyses of the integrated viral DNA revealed an early region of 4.4 kilobases instead of the lytic-size 2.7 kilobases. However, upon subcloning in either plastic or agarose or after being in culture for several passages, the appearance of lytic-size large T and small t antigens was detected. Concurrently, an early region of 2.7 kilobases, in addition to one of 4.4 kilobases, was observed.